Hospital classroom, home care and educational centre: different spaces, an inclusive educational project - Cardell Ortus, Artur; Quirós Menéndez, Eva (Avances en Supervisión Educativa, 2023)
Hospital and home care in Spain is a service offered by the Administration that contributes to the inclusion and equity of pupils who, due to their health condition, cannot access the regular education system. This educational care is based on the principles of quality, equity and equal opportunities; individualisation; coordination and collaboration of all those involved (educational centre, family, teaching and health staff); maintaining the emotional and social links of sick or convalescent pupils with their community of reference, using innovative and pupil-centred methodologies. Each Autonomous Community, within its competences, organizes this hospital and home care. The Education Inspectorate, in accordance with the functions assigned to it, must supervise and advise on the care of pupils with health problems.